2018
DOI: 10.7150/ntno.24590
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Transcriptional Analysis of Oxidative Stress-related Genes and Pathways Induced by CdTe aqQDs in Mice

Abstract: Objective: Quantum dots (QDs) has widely applied in the field of science, whose potential toxic effect has increasingly become a focus concern we need pay attention to in public health. The purpose of this article was to explore the toxicity mechanism with oxidative damage from treatment with QDs at the molecular level through a gene microarray.Methods: Mice were administered aqueously synthesized cadmium telluride QDs (CdTe aqQDs) via intravenous tail injection of a 2 µmol/kg solution (based on the molar mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…48 The RAS pathway is strongly modulated in HepG2 cells, 49 liver injury, and chronic liver diseases. 50,51 Furthermore, activation of integrin and focal adhesion kinase (FAK) signaling pathways, as observed here, suggests regulation of cell migration, cell proliferation, and angiogenesis, all of which are known to contribute to carcinogenesis in different cell types. [52][53][54] Genes involved in epithelial-mesenchymal transition (EMT) and G1/S checkpoint regulatory pathways were also noticeably upregulated, highlighting the potential for fibrosis, cancer progression 55 and oncogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…48 The RAS pathway is strongly modulated in HepG2 cells, 49 liver injury, and chronic liver diseases. 50,51 Furthermore, activation of integrin and focal adhesion kinase (FAK) signaling pathways, as observed here, suggests regulation of cell migration, cell proliferation, and angiogenesis, all of which are known to contribute to carcinogenesis in different cell types. [52][53][54] Genes involved in epithelial-mesenchymal transition (EMT) and G1/S checkpoint regulatory pathways were also noticeably upregulated, highlighting the potential for fibrosis, cancer progression 55 and oncogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…The toxicity of CuO and Ag could arise from the release of toxic ions from the materials and/or oxidative stress through production of ROS. [ 18–21 ] However, free ion toxicity in the BAL seems unlikely as the maximum dissolution rates of the CuO material are <0.4% (3.67, 2.00, 1.81 and 3.71 µg min –1 from 800 µg of metal for CuO core , CuO NH2 , CUO COOH, and CuO PEG respectively, see Vassallo et al. 2018.…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity of CuO and Ag could arise from the release of toxic ions from the materials and/or oxidative stress through production of ROS. [18][19][20][21] However, free ion toxicity in the BAL seems unlikely as the maximum dissolution rates of the CuO material are <0.4% (3.67, 2.00, 1.81 and 3.71 µg min -1 from 800 µg of metal for CuO core , CuO NH2 , CUO COOH, and CuO PEG respectively, see Vassallo et al 2018. Nonetheless, irritation of sensory nerves during Cu exposure is known to stimulate both adrenergic pathways and cortisol secretion, leading to a wider stress response and inflammation.…”
Section: Immune Cell Influx and Lung Histology Suggest Immunotoxic Po...mentioning
confidence: 99%
“…Furthermore, P450scc protein synthesis plays a crucial role in the synthesis of both pregnenolone and testosterone. Several authors reported that the Cyp11a1 gene may increase extra-gonadal tissues following oxidative stress induced by NPs [28]. In contrast to these findings, Dziendzikowska et al [3] demonstrated that a single intravenous administration of 20 nm AgNPs resulted in a significant decrease in Cyp11a1 and Hsd3b1 gene expressions and lowered testosterone and DHT levels in testes, compared to control animals 28 days after a single exposure.…”
Section: Discussionmentioning
confidence: 97%